1988
DOI: 10.1002/1097-4679(198807)44:4<573::aid-jclp2270440414>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

The comparative recidivism rates of voluntary- and coerced admission male alcoholics

Abstract: The outcomes of inpatient alcoholics who reported that they had been coerced into treatment by commitment or pressure from others were compared in a follow‐up study to those of alcoholics who described themselves as voluntary admissions. Ten assessments of control over drinking, number of drinking days in the past week, and intoxication since previous appraisal were made by collaterals between 2 weeks and 18 months after treatment. Even though the data were analyzed in several ways, the number of significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…Mandated treatment works at least as well as bvoluntaryQ treatment (Dembo et al, 1993;Hall, 1997;Rotgers, 1992;Watson, Brown, Tilleskjor, Jacobs, & Pucel, 1989), and higher treatment gains are found for adolescent offenders compared to adult offenders (Day, Howells, & Rickwood, 2004). It is necessary that programs be of sufficient intensity and treatment integrity to meet the treatment needs of young people.…”
Section: Discussionmentioning
confidence: 99%
“…Mandated treatment works at least as well as bvoluntaryQ treatment (Dembo et al, 1993;Hall, 1997;Rotgers, 1992;Watson, Brown, Tilleskjor, Jacobs, & Pucel, 1989), and higher treatment gains are found for adolescent offenders compared to adult offenders (Day, Howells, & Rickwood, 2004). It is necessary that programs be of sufficient intensity and treatment integrity to meet the treatment needs of young people.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that, after an average of 29 weeks of involuntary commitment, subjects were able to maintain abstinence, felt the severity of their alcohol problems were less, and that commitment was well tolerated. Watson et al analyzed treatment outcomes after completion of an inpatient alcohol treatment program and found little difference between coerced and self-referred patients (15). However, others have found that patients who had been coerced into a residential treatment program stayed longer than those who had enrolled voluntarily (7).…”
Section: Discussionmentioning
confidence: 99%
“…Within North America, several studies have concluded that legal pressure has a strong and positive impact on treatment entry and, subsequently, retention and positive outcomes. [56][57][58][59] Indeed, three of these studies suggest significantly improved performance for legally referred compared with voluntary clients However, it should be noted that they relate to either primary alcohol users, 59 adolescents in specialist (CJS referral only) residential units 58 or female offenders serving out alternatives to custody and/or child custody procedures. 56 Each of these represents a specific set of circumstances and motivational issues.…”
Section: Rationale For This Studymentioning
confidence: 99%
“…[59][60][61][62] Again, the context of these studies varies and two of these 59,60 were concerned with adolescents or primary alcohol users only. There is also literature that theorises the possible negative results of a policy of criminal justice referrals into treatment based on presumptions of need and non-empirical evidence bases.…”
Section: Rationale For This Studymentioning
confidence: 99%